PERSPEKTIF HUKUM SIBER DI INDONESIA: PENANGANAN KASUS CYBER TERHADAP TANDA TANGAN ELEKTRONIK - Aas Rohmat; Ismiyanto; Muhammad Muhtarom (LP3M, 2022)
In the era of globalization, society 5.0 technology, followed by the development of information technology in cyber space, is something that cannot be avoided. This is followed by the vulnerability of threats and attacks on data and information traffic that can threaten state sovereignty. The security factor is the main obstacle in line with the increasing level of crime in cyberspace in Indonesia. The purpose of this study is the Perspective of Cyber Law in Indonesia: Handling Cyber Cases Against Electronic Signatures. The research method used in this research is descriptive. The type of research that the author uses is normative legal research or known as doctrinal legal research which is commonly referred to as legal research or legal research instructions. This legal research examines library material obtained through literature review by collecting and studying primary and secondary legal materials in the form of laws and literature that are relevant to the research object. The approaches used in this legal research are statutory and contextual approaches. The analysis used is descriptive, namely to describe or explain the phenomenon under study. The analysis is carried out by linking causes and effects to the emergence of the phenomenon under study. The findings in this study are that the perspective of cyber law in Indonesia in handling cyber cases against data theft or threats related to electronic signatures is very important to be immediately normalized.